A Novel Chaotic Switched Modulation for EMI Suppression in Electrical Drive System - Asker, Mehmet Emin; Kürüm, Hasan (My University, 2021)
In electric drive systems common mod voltage (CMV) is known as voltage between power line and ground. CMV causes negative effects on both electric engine and its driver whereas switching operation occurs in power devices. In addition switching frequency and its multiples in CMV cause electromagnetic and aqustic noises. In this paper a novel FixedFrequency chaotic switched sinusoidal pulse width modulation (FFCS-SPWM) is proposed. The cruial point in proposed FFCSSPWM method is to obtained a new carrier wave by summation of carrier wave and its inverse form. In FFCS-SPWM method extra switching loses were reduced due to constant switching frequency. This method also applied to permanent magnet synchronous motor (PMSM) vector control system. The reduction of electromagnetic interference (EMI), aqustic noises and dv/dt stress effects that occur in CMV is simulated by proposed method. Moreover SPWM combined with chaoticfrequency chaotic switched (CFCS) is proposed to reduce the differential mode voltage (DMV) which occurs due to voltage between lines. Finally in this method switching frequency change chaotically and also in this paper it shown that, CFCS-SPWM provides to reduce EMI, aqustic noises which are caused by CMV and DMV.
Keywords: Mühendislik; Elektrik ve Elektronik